2012
DOI: 10.1051/0004-6361/201117423
|View full text |Cite
|
Sign up to set email alerts
|

Loops formed by tidal tails as fossil records of a major merger

Abstract: Context. Many haloes of nearby disc galaxies contain faint and extended features, including loops, which are often interpreted as relics of satellite infall in the main galaxy's potential well. In most cases, however, the residual nucleus of the satellite is not seen, although it is predicted by numerical simulations. Aims. We test whether such faint and extended features can be associated to gas-rich, major mergers, which may also lead to disc rebuilding and thus be a corner stone for the formation of spiral … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(92 citation statements)
references
References 89 publications
2
82
0
Order By: Relevance
“…The stellar stream in NGC 5907 has been previously modeled with a satellite galaxy accretion event (Martínez-Delgado et al 2008, total mass ratio 1:4000) and with a gasrich major galaxy merger (Wang et al 2012, total mass ratio Figure 7) through the data (black) and extended PSF background models (blue and red colors) crossing the plane of NGC 5907 and along the stellar stream. The slices are plotted as a function of distance from the galaxy midplane.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The stellar stream in NGC 5907 has been previously modeled with a satellite galaxy accretion event (Martínez-Delgado et al 2008, total mass ratio 1:4000) and with a gasrich major galaxy merger (Wang et al 2012, total mass ratio Figure 7) through the data (black) and extended PSF background models (blue and red colors) crossing the plane of NGC 5907 and along the stellar stream. The slices are plotted as a function of distance from the galaxy midplane.…”
Section: Discussionmentioning
confidence: 99%
“…Martínez-Delgado et al (2008) also produced a simple N-body model that mimicked the observed loopy stellar stream as a fossil of the tidal disruption of a single satellite in a merger event (total mass ratio of 1:4000), rejecting the hypothesis of multiple merger events in the halo of NGC 5907. In contrast, Wang et al (2012) reported a model that reproduced the general structure of the stellar stream around NGC5907 in a major merger scenario. Wang et al (2012) suggested that the colors of the stream may be used to distinguish between a minor satellite accretion event and a major merger origin of the stellar stream in NGC5907 (the stream is too faint to be observed spectroscopically).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Martínez-Delgado et al (2008) modeled the stellar stream with a satellite companion having a stellar mass of ≈ 3.5× 10 8 M . In contrast, Wang et al (2012) modeled the stream with a major merger (mass ratio 1:3 -1:12). While our relatively high metallicity value suggests a major merger origin of the stream, it is possible that the metallicity is consistent with a satellite accretion event such as the Sagittarius Stream (Chou et al 2007) or the giant stream in M31 (Kalirai et al 2006).…”
Section: Observations Data Reduction and Resultsmentioning
confidence: 99%
“…There are now many simulations of disk formation via gas-rich mergers, including in the cosmological context [36]. They naturally produce an important thick disk component that is made of material re-accreted by the newly re-formed galaxy [15,38].…”
Section: Conclusion: What Can We Learn On and From The Milky Way Formmentioning
confidence: 99%